2017
DOI: 10.24925/turjaf.v5i5.459-463.883
|View full text |Cite
|
Sign up to set email alerts
|

Determining Chemical Composition and Rumen Degradation Characteristics of Different Chickpea (Cicer Arietinum L.) Lines Straw

Abstract: This study aimed to identfy chemical composition, ruminal degradation characeristics and metabolizable energy (ME) content of five different chickpea line and a check cultivar's straw using nylon bag technique. Feed samples were incubated as three replicates of each fistulated Holstein heifer for 0, 8, 12, 24, 36, 48, 72 and 96 h. Degradation characteristics of dry matter (DM) and neutral detergent fiber (NDF) in rumen were determined by using this mathematical expression D=a+b(1-e -ct ). Crude protein (CP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…The differences in EDDM between the varieties can be mainly attributed to the differences in A fraction and not to B and C fractions, which is consistent with the literature [47]. The EDDM reported for common vetch straw in our study are similar to that reported for chickpea straw (51.8% DM) [49], but greater than that reported for fenugreek ( Trigonella foenum-graecum ) straw (32.2% DM) [50]. The degradation profiles of NDF were not influenced by variety in our study, which is in agreement with the earlier reports on maize and chickpea [47,49].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The differences in EDDM between the varieties can be mainly attributed to the differences in A fraction and not to B and C fractions, which is consistent with the literature [47]. The EDDM reported for common vetch straw in our study are similar to that reported for chickpea straw (51.8% DM) [49], but greater than that reported for fenugreek ( Trigonella foenum-graecum ) straw (32.2% DM) [50]. The degradation profiles of NDF were not influenced by variety in our study, which is in agreement with the earlier reports on maize and chickpea [47,49].…”
Section: Discussionsupporting
confidence: 92%
“…The EDDM reported for common vetch straw in our study are similar to that reported for chickpea straw (51.8% DM) [49], but greater than that reported for fenugreek ( Trigonella foenum-graecum ) straw (32.2% DM) [50]. The degradation profiles of NDF were not influenced by variety in our study, which is in agreement with the earlier reports on maize and chickpea [47,49]. Bruno-Soares et al [48] reported less rapidly degradable NDF fraction and rate of NDF degradation, and similar potentially degradable NDF fraction in comparison with those observed in this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation